An oral and maxillofacial surgery pro forma for improving compliance with sepsis six. (17th October 2020) - Collins, L.; Beech, A.N.; Gormley, M.; Farrier, J.N.
Abstract: Background: Patients presenting to the Oral and Maxillofacial Surgery (OMFS) department with odontogenic or cervico‐facial infections are at risk of sepsis. The Sepsis Six bundle significantly reduces mortality if completed within 1 h. This study describes the use of a novel pro forma for OMFS which aims to improve compliance with Sepsis Six. Methods: A pilot retrospective audit was completed to determine compliance with the Sepsis Six bundle. Data were collected from consecutive patient case notes referred to a single UK OMFS department. A custom pro forma sheet was designed. Two further audit cycles were carried out over a 4‐year period and dental core trainees focus group gave feedback on the new pro forma. Results: A pilot retrospective audit showed no compliance with the original Sepsis Six bundle. Completion of the new pro forma for patients presenting with cervico‐facial and odontogenic infection increased to 59% in the second cycle. There was a 66% increase in the delivery of intravenous antibiotics within the first hour and lactate measurement rose to 50% by the second cycle. Importantly, initial observation of vital signs improved throughout the audit, reaching 97%. The focus group generally supported improvements in compliance, effective communication, and good record‐keeping using the pro forma. Conclusion: The introduction of a custom pro forma for OMFS appears to improve completion of the Sepsis Six bundle which could reduce morbidity and mortality. Continual team education is required, and further audit would be useful to determine if this intervention alone is the reason for increased compliance.